Association between perceived level of autonomy and perceived behavioural control over resolving ethical dilemmas: A large N cross-sectional survey of Canadian civil servants - Jacob, Steve; Ouimet, Mathieu (Revue Gouvernance / Governance Review, 2015)
Inspired by the theory of planned behaviour (Ajzen 1991), this study examines the relationship between the perceived level of autonomy among civil servants and their perceived behavioural control over the resolution process of work-related ethical dilemmas. To this end, we used a subset of the data from the 2008 Statistics Canada Public Service Employee Survey (PSES). This cross-sectional survey was conducted between November 3 and December 12, 2008. Approximately 170,000 employees responded to the survey, representing 66 percent of the 258,000 employees invited to participate. In summary, the perceived level of autonomy index is positively associated with the perceived behavioural control over the resolution of ethical dilemmas, as was theoretically expected.